Clinical biochemistry and drug development : from fundamentals to output - Kumar, Shashank (Burlington, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2021)
"This book, Clinical Biochemistry and Drug Development: From Fundamentals to Output, focuses on clinical biochemistry fundamentals, cell culture techniques, and drug discovery and development concepts. It deals with three different fields of clinical research: cell culture, clinical biochemistry, and drug discovery and development. The book introduces cell animal and bacterial culture techniques and their potential uses as well as cell culture techniques. The biochemistry aspect of the book covers the principles of clinical biochemistry and biochemical analysis, biochemical aids to clinical diagnosis, measurement, and quality control. The book also presents important concepts in cell membrane receptor signal transduction pathways as drug targets. The drug development focus of the book discusses the fundamentals of human disease and drug discovery. Various in silico, in vitro, and in vivo approaches for drug discovery are examined, along with a discussion on drug delivery carriers and clinical trials. Overall, the volume provides an overview of the journey from clinical fundamentals to clinical output. The book aims to provide an understanding for the students of health science and life sciences. This book involves the fundamentals of clinical biochemistry and use of cell culture techniques. Furthermore the book will discuss the fundamentals of drug discovery and development."--
An Introduction to Cell Culture / Amit Kumar Sharma, Atul Kumar Singh, and Shashank Kumar -- Animal Cell Culture / Amit Kumar Sharma, Atul Kumar Singh, Mohammad Waseem, and Shashank Kumar -- Bacterial Cell Culture / Amit Kumar Sharma, Santosh Kumar Maurya, and Shashank Kumar -- Potential Use of Cell Cultures / Amit Kumar Sharma, Atul Kumar Singh, Hadiya Husain, and Shashank Kumar -- Principles of Clinical Biochemistry and Biochemical Analysis / Shashank Kumar -- Biochemical Aids to Clinical Diagnosis / Prem Prakash Kushwaha, P. Seshu Vardhan, K. Vishnupriya, Sharmistha Singh, and Shashank Kumar -- Clinical Measurements and Quality Control / Prem Prakash Kushwaha, P. Seshu Vardhan, M.S. Sandeep Vedanarayana, and Shashank Kumar -- Cell Membrane Receptor / Prem Prakash Kushwaha, Swastika Dash, Atul Kumar Singh, and Shashank Kumar -- Mechanisms of Signal Transduction / Prem Prakash Kushwaha, Rebati Malik, P. Seshu Vardhan, Shiv Govind Rawat, Sharmistha Singh, and Shashank Kumar -- Human Disease Drug Therapy and Drug Discovery / Prem Prakash Kushwaha, Rebati Malik, P. Seshu Vardhan, Shiv Govind Rawat, Atul Kumar Singh, and Shashank Kumar -- Drug Development: In Silico, In Vivo, and System Biology Approach / Prem Prakash Kushwaha, Rebati Malik, Shiv Govind Rawat, Atul Kumar Singh, and Shashank Kumar -- Drug Development: Drug Delivery Carriers and Clinical Trial / Prem Prakash Kushwaha, Swagata Das, Atul Kumar Singh, and Shashank Kumar -- Role of Micro RNA in Prostate Cancer Therapy / Mohammad Waseem, Hadiya Husain, and Imran Ahmad -- Pathogenesis, Molecular Mechanisms of Progression, and Therapeutic Targets of Liver Fibrosis: An Update / Hadiya Husain and Riaz Ahmad -- Prostate Cancer: Molecular Aspects, Biomarkers, and Chemo-Preventive Agents / Risha Ganguly, Abhay K. Pandey, Prem Prakash Kushwaha, and Shashank Kumar -- Overview of Tuberculosis Biomarkers: An Update / Abhilasha Tripathi, Surya Kant, Prem Prakash Kushwaha, and Shashank Kumar.
OCLC-licensed vendor bibliographic record.
Keywords: Clinical biochemistry; Cell culture; Drug development; MEDICAL / Biochemistry; MEDICAL / Pharmacology; MEDICAL / Pharmacy